Investigation of non-equilibrium turbulence decay in the atmospheric boundary layer using Doppler lidar measurements - M. Karasewicz; M. Wacławczyk; P. Ortiz-Amezcua; Ł. Janicka; P. Poczta; P. Poczta; C. Kassar Borges; I. S. Stachlewska (Atmospheric Chemistry and Physics)
This work concerns analysis of turbulence in the atmospheric boundary layer (ABL) shortly before and after sunset. Based on a large set of Doppler lidar measurements at rural and urban sites, we analyze frequency spectra of vertical wind at different heights and show that they increasingly deviate from Kolmogorov's -5/3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="28pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c010f45c8d9a823a56ed826ff72bac29"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-13231-2024-ie00001.svg" width="28pt" height="14pt" src="acp-24-13231-2024-ie00001.png"/></svg:svg> prediction in the measured low-wavenumber part of the inertial range. We find that before sunset, the integral length scales tend to decrease with time. These findings contrast with a classical model of equilibrium decay of isotropic turbulence, which predicts that the scaling exponent should remain constant and equal to -5/3<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="28pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="fa0e74ec8cb07aa6650e6f2d65de63f0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-24-13231-2024-ie00002.svg" width="28pt" height="14pt" src="acp-24-13231-2024-ie00002.png"/></svg:svg> and the integral length scale should increase in time. We explain the observations using recent theories of non-equilibrium turbulence. The presence of non-equilibrium suggests that classical parametrization schemes fail to predict turbulence statistics shortly before sunset. By comparing the classical and the non-equilibrium models, we conclude that the former may underestimate the dissipation rate of turbulence kinetic energy in the initial stages of decay.